GAMBARAN RIWAYAT POLA MAKAN DAN STATUS GIZI PASIEN DIABETES MELITUS TIPE 2 RAWAT JALAN PESERTA JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) DI RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Suhaema Suhaema; Ni Ketut Sri Sulendri Sulendri; Tira Septiana (poltekkes kemenkes mataram, 2015)
Abstract: Background :Diabetes Mellitus (DM) is which one of chronic disease, the prevalention increase of in universal including in Indonesia. The diabetic patients not only the society economic high class but from the society of low class. The prediction of WHO is totally increase diabetic patient in Indonesia from 8.4 million in years 2000 became 21.3 million in years 2030.Purpose : To knowing the dietary history and nutrient status of type 2 diabetes mellitus in out patients of goverment insurance (JAMKESMAS) in hospital city of mataram.Method : This study is an observational description with cross-sectional design. The sample is patients type 2 DM out patients member of JAMKESMAS in Nutrition Clinic of Hospital Mataram with or nothing complication disease from 2 years ago and 20-75 years old. Totally sample is 37.Result :The sample are>45 years old (78.4%), female (73%), new diagnosed <1 year (24.3%). Sample has disease family history (37.8%), physical activity are active (70.3%) and inactive (29.7%), and hypertention (40.5%). Dietary history in accustomed frequency carbohidrate (62.2%) and fat (59.5%), then frequency often is protein(73%) and fiber (48.6%). The nutrient status of 40.5% sample is overweight (BMI ≥23.0 kg/m2), and based of body fat percentageis obesity (37.8%).